METAL STRUCTURES SURVIVABILITY ASSESSMENT WHEN SIMULATING SERVICE CONDITIONS - Gibalenko, O. M.; Trofymchuk, T. S. (Science and Transport Progress, 2016)
Purpose. The research is aimed at improving the quality and reliability of measures of primary and secondary protection of metal structures at manufacturing companies, to prolong the service life of cyclically loaded structures of production facilities taking into account the corrosion level of danger. Methodology. Authors proposed to use the principles of process approach for statement and realization of management problems of operational service life in corrosion environments. The principles of ensuring reliability on the level of corrosion danger include justification of stages sequence for survivability assessment of a structural metalwork based on the strategy of DMAIC (define, measure, analyze, improve, control): definitions, measurements, analysis, improvement and monitoring of measures of primary and secondary corrosion protection. Findings. Providing control measures from corrosion according to the criterion of corrosion danger allows providing requirements of reliability of structural metalwork based on calculated provisions of the limiting conditions method and solving the problems of management in technological safety during the expected service life of structural objects. Originality. The developed strategy of maintenance of the industrial facilities on an actual state includes the process approach to resource management by creation of system for the account and the functional controlling, risk analysis and regulation of technological safety in production facilities of the enterprises. Realization of the principles of process approach to management of technological safety at the object level is directed to perfecting of tools and methods of anticorrosive protection, extension of a resource taking into account indexes of survivability (,) and justification of program measures to ensure the reliability of enterprises(PER). Practical value. On the basis of process approach to quality and reliability management, generalizations of the natural and numerical researches directed to justification of design solutions of primary and secondary protection of a metalwork at the given level of corrosion danger of a metalwork the organizational measures of PER including assessment of integral characteristics of constructional suitability, technological rationality and risk analysis of signs corrosion danger of objects are developed.